Elites in El Salvador: Changes and continuities in the last decade (2000-2016) - Robles Rivera, Francisco (2017)
This article analyzes the changes and continuities in the economic elites in El Salvador in the last decade, as well as their main changes in the axes of accumulation. It is argued that unlike what was foreseen at the beginning of the 1990s, the trade liberalization and the sale of Salvadoran private companies have modified the axes of accumulation. In this regard, economic elites have focused their interests mainly to the economies related with remittances and services. Finally, the impact of the leftits governments (FMLN) and the emergence of new economic agents linked to the ALBA petroleos project is briefly discussed.